Synonymy and lexical variation in Spanish and Italian phraseology: proposal for an online bilingual bidirectional dictionary - Dal Maso, Elena (Círculo de Lingüística Aplicada a la Comunicación, 2020)
This article presents a lexicographical proposal focused on lexical variation and synonymy in Spanish and Italian idioms. The purpose of this proposal is twofold: firstly, to put forward a possible strategy for the lemmatization of lexical variation and synonymy in dictionaries of idioms, and, secondly, to contribute to the development of Spanish/Italian bilingual phraseography by offering some patterns for lexicographical records in digital format. As a result, in the first part of this essay we describe the methodology used in order to select and analyse the idioms; then, in the second part, we propose lexicographical records for the elaboration of an online dictionary of idioms – currently in progress –based on the functional equivalence criterion (Mellado Blanco 2015) and the lexicographical proposal illustrated in Lončar and Dal Maso (2018) y Dal Maso (2019).